2023
DOI: 10.3390/foods12183334
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Betaphycus gelatinum Using Lactobacillus brevis: Growth of Probiotics, Total Polyphenol Content, Polyphenol Profile, and Antioxidant Capacity

Zhe Wang,
Caibo Zhao,
Zhiqiang Guo
et al.

Abstract: Little information is available regarding polyphenol variations in the food processing of edible and medicinal red seaweed, Betaphycus gelatinum. This study investigated the effects of Lactobacillus brevis fermentation on total polyphenol content (TPC), polyphenol profile, and antioxidant activity in Betaphycus gelatinum pretreated by ultrasound-assisted mild acid hydrolysis for the first time. During 60 h of fermentation, the viable colony number significantly increased, pH significantly decreased, and reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Flavonoids and their derivatives are considered among the most abundant phenolic compounds in different types of seaweed [ 48 , 49 ]. These compounds exhibit various biological activities and can be used in the prevention of many human diseases [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids and their derivatives are considered among the most abundant phenolic compounds in different types of seaweed [ 48 , 49 ]. These compounds exhibit various biological activities and can be used in the prevention of many human diseases [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [48] confirmed the presence of this compound in the seaweed extracts, including the alcoholic extract of Sargassum polycystum from the South China Sea. Flavonoids and their derivatives are considered among the most abundant phenolic compounds in different types of seaweed [48,49]. These compounds exhibit various biological activities and can be used in the prevention of many human diseases [50].…”
Section: Identification Of Extracts' Chemical Constituents Via the Ch...mentioning
confidence: 99%